Pengaruh Promosi Penjualan, Variasi Produk Dan Kualitas Pelayanan Terhadap Minat Beli Ulang Pada Butik Kanabini Di Tenggarong - Desi Peburiyanti; Sabran Sabran (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
This study aimed to analyze the influence of sales promotion, product variation and service quality of repurchase interest. Respondents who are involved on this study were 64 respondents. While this study used non-probability sampling. The number of independent variables studied were 3 namely sales promotion , product variation and service quality with 1 dependent variable namely repurchase intention. Data collection is done by distributing questionnaires and the analytical method used in this study is multiple linear regression with the help of SPSS statistics 23. From the results of the t test (partial) show that variabel sales promotion (x1) and product variation (x2) is rejected, it’s mean the variables has no effect on repurchase interes. On variable service quality (x3) is accepted, it’s mean this variable declared to have an effect on repurchase interest and proven truth, this statement is reinforced by the values described or explained earlier in the t test table (partial ) at the KanaBini Boutique in Tenggarong. Keywords : Sales Promotion, Product Variation, Service Quality and Repurchase Interest.